(untitled) (Open Herald: Periodical of Methodical Research, 2024)
This article provides recommendations on the organization of independent educational work in higher military educational institutions. The goals and tasks of independent education are indicated. Also, ways to increase the efficiency of independent educational work have been revealed. It is mentioned in this article that the proper organization of independent educational work serves to form deep and solid knowledge in the training of future family military specialists.